Pemikiran Tokoh Islamisasi Ilmu Pengetahuan: (Syed Muhammad Naquib Al-Attas) - Ifa Afida (FALASIFA : Jurnal Studi Keislaman, 2016)
Syed Muhammad Naquib Al-Attas, including one Islamic thinkers and educational reformer with fresh ideas. Al-Attas not only as an intellectual concern to education and the general question of Muslims, but also experts in various fields of science. He is also regarded as a figure of the initiators of the Islamization of science that affects many other figures. He systematically formulate strategies in the form of Islamization of the educational curriculum for Muslims. Nevertheless, the ideas of Al-Attas Islamization of science in Islamic education. Many of thinkers challenged born of the Western world. Regardless, Al-Attas has been known as the philosopher of Islamic education which until recently famous among the Muslims of the world and also as a figure reformer (person of reform) Islamic education. Positive or negative response of the intellectuals addressed to Al-Attas made the study of the thoughts of Al-Attas increasingly attractive. Keywords: Thought Naquib Al-Attas, Islamization of Sciences